Blood from stone - Fyfield, Frances (Sphere, 2009)
Marianne Shearer is at the height of her career, a dauntingly successful barrister, respected by her peers and revered by her clients.So why has she killed herself?Her latest case had again resulted in an acquittal, although the outcome was principally due to the death of the prime witness after Marianne's forceful cross-examination.Had this wholly professional and unemotional lawyer been struck by guilt or uncertainty, or is there some secret to be discovered in her blandly comfortable private life?Her tenacious colleague Peter Friel is determined to find out of that last trial held the reason for her taking her own life.The transcript holds intriguing clues, but it is another witness at the trial who holds the key to the truth.